Pengembangan Usaha Budidaya Ikan Lele (Clarias sp.) di Lahan Kering di Kabupaten Gunungkidul, Provinsi Daerah Istimewa Yogyakarta - Denny Jatnika; Komar Sumantadinata; Nora Herdiana Pandjaitan (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2014)
The one commodity that is highly prospective for cultivated on an industrial scale and households are catfish (Clarias sp.). The purpose of this study was (1) analyze the feasibility of catfish farming in dry land in the district of Gunung Kidul Yogyakarta Province, (2) analyze the potential of catfish farming in ponds tarp on dry land, (3) develop alternative business development in the district of Gunung Kidul Yogyakarta Province. The method used in this thesis is descriptive method that focuses on technical aspects and business cultivation, as well as a SWOT analysis. Based on the feasibility analysis has a promising prospect and deserves to be developed. To maximize revenue catfish farmers, a combination of strategies SO, WO Strategies and strategy ST is an appropriate strategy to be chosen by farmers to improve their business. Increase the number and extent of ponds and develop farming, applying methods of maintenance and cultivation of good, as well as expand market coverage ranging from individual consumers, restaurants and traditional markets to restaurants to modern markets to improve capital efficiency and increase profits for farmers catfish on dry land in the district of Gunung Kidul.